The Primitive Thylakoid-Less Cyanobacterium Gloeobacter Is a Common Rock-Dwelling Organism - Mareš, Jan; Hrouzek, Pavel; Kaňa, Radek; Ventura, Stefano; Strunecký, Otakar; Komárek, Jiří (PloS one, 2013)
Cyanobacteria are an ancient group of photosynthetic prokaryotes, which are significant in biogeochemical cycles. The most primitive among living cyanobacteria, Gloeobacter violaceus, shows a unique ancestral cell organization with a complete absence of inner membranes (thylakoids) and an uncommon structure of the photosynthetic apparatus. Numerous phylogenetic papers proved its basal position among all of the organisms and organelles capable of plant-like photosynthesis (i.e., cyanobacteria, chloroplasts of algae and plants). Hence, G. violaceus has become one of the key species in evolutionary study of photosynthetic life. It also numbers among the most widely used organisms in experimental photosynthesis research. Except for a few related culture isolates, there has been little data on the actual biology of Gloeobacter, being relegated to an "evolutionary curiosity" with an enigmatic identity. Here we show that members of the genus Gloeobacter probably are common rock-dwelling cyanobacteria. On the basis of morphological, ultrastructural, pigment, and phylogenetic comparisons of available Gloeobacter strains, as well as on the basis of three new independent isolates and historical type specimen, we have produced strong evidence as to the close relationship of Gloeobacter to a long known rock-dwelling cyanobacterial morphospecies Aphanothece caldariorum. Our results bring new clues to solving the 40 year old puzzle of the true biological identity of Gloeobacter violaceus, a model organism with a high value in several biological disciplines. A probable broader distribution of Gloeobacter in common wet-rock habitats worldwide is suggested by our data, and its ecological meaning is discussed taking into consideration the background of cyanobacterial evolution. We provide observations of previously unknown genetic variability and phenotypic plasticity, which we expect to be utilized by experimental and evolutionary researchers worldwide.
Keywords: Thylakoids; Cyanobacteria; Phylogeny; RNA, Ribosomal; RNA ribozomální; sinice; fylogeneze; tylakoidy